Competence and Workload of Forensic Non-Medical Workers during the COVID-19 Pandemic - Fitri Ambar Sari; Made Ayu Mira Wiryaningsih (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
This study aims to understand strategies needed to overcome competency and workload challenges faced by non-medical workers in the Forensic Unit of the Universitas Indonesia Hospital (RSUI). This descriptive study was performed in the Forensic Unit of RSUI in March 2021. Respondents were chosen by purposive sampling, consisting of three non-medical staff from the unit. Data was collected from the forensic unit, human resources department, and direct observation for three days using the Time and Motion Study Observation Method and structured interviews with each respondent. The subjects of this study were three non-medical workers (two forensic technicians and one mortuary personnel) of the Forensics Unit, all males; each graduated from high school and has attended non-formal training or workshops which support their job position in the unit. Since the pandemic, there has been an increase in the number of services conducted by the unit, especially mortuary and funeral services. The proportion of productivity based on the three-day observation during office hours was 80%, 80%, and 30%, while the after-office hours (during the on-call schedule) were 96%, 96%, and 88%.